2019
DOI: 10.1002/ajmg.a.61387
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and perinatal history in Kabuki Syndrome

Abstract: Kabuki syndrome (KS) is a disorder of epigenetic dysregulation due to heterozygous mutations in KMT2D or KDM6A, genes encoding a lysine-specific methyltransferase or demethylase, respectively. The phenotype is highly variable, including congenital cardiac and renal anomalies, developmental delay, hypotonia, failure to thrive, short stature, and immune dysfunction. All affected individuals have characteristic facial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Ultrasound scans showed a range of abnormalities including increased nuchal translucency, pleural effusion, cardiac anomaly, renal anomalies, intrauterine growth restriction, polyhydramnios, oligohydramnios and single umbilical artery. Similar antenatal presentations were also noted in the recent large case series and published case reports 8–40 . More than half of the cases were diagnosed after birth by clinical assessment and molecular testing.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Ultrasound scans showed a range of abnormalities including increased nuchal translucency, pleural effusion, cardiac anomaly, renal anomalies, intrauterine growth restriction, polyhydramnios, oligohydramnios and single umbilical artery. Similar antenatal presentations were also noted in the recent large case series and published case reports 8–40 . More than half of the cases were diagnosed after birth by clinical assessment and molecular testing.…”
Section: Discussionsupporting
confidence: 78%
“…In the prenatal setting, the congenital anomalies related to KS may be detectable on routine antenatal ultrasound examination. Some case reports and case series about antenatal sonographic features of postnatal confirmed KS patients have appeared in the literature 8–10 . With advancement in prenatal molecular technologies and discovery of causative genes, this syndrome can be diagnosed by next generation sequencing techniques in prenatal genetic testing.…”
Section: Introductionmentioning
confidence: 99%
“…Fewer than 10% of patients with KS1 and/or clinically diagnosed KS have IUGR. 28 Interestingly 11 of 13 patients in our cohort known to have been born prematurely (before 37 weeks of gestation) were males. Birth length and HC in patients with pathogenic KDM6A variants were observed to be in normal-to-low range.…”
Section: Discussionmentioning
confidence: 88%
“…It is interesting that the most common syndromes in this study were Kabuki and CHARGE. Kabuki syndrome has a highly variable phenotype 33 . There is limited evidence with regard to its prenatal presentation, and the high incidence seen in this study has not been reported previously, although an overall association with postnatally diagnosed left-sided CHD has been established [33][34][35] .…”
Section: Discussionmentioning
confidence: 99%